Comparative Study of Farming Practices on the Productivity and Morphological Characteristics of Repeatedly Cultivated Soybeans - Wang, Tian; Xu, Naibo; Mao, Tingyong; Liu, Jiahao; Wang, Deisheng; Zhai, Yunlong (International Journal of Natural Resources and Environmental Studies, 2024)
This study aims to compare the impact of different farming practices on the productivity and morphological characteristics of repeatedly cultivated soybeans. Through systematic field surveys and data analysis, we contrasted the effects of various agricultural cultivation practices on soybean cultivation. The results indicate significant differences in soybean productivity and morphological characteristics among different farming practices, providing insights for optimizing cultivation methods. This study contributes to improving the efficiency and yield of soybean cultivation, offering valuable insights for agricultural production.